Kalevi Aho: Alles Vergängliche - Symphony for organ - Three interludes for organ - Aho, Kalevi; Lehtola, Jan (Akersberga, Sweden BIS Records AB, 2012)
Largely known and admired for his large orchestral scores including fifteen symphonies to date the Finnish composer Kalevi Aho has actually written in a wide variety of genres, including chamber music and opera. He did arrive at the organ via the orchestra, however: in 1993, when composing his Eighth Symphony, he decided to let the organ feature in it as a solo instrument. Although he integrated it into the orchestra, it was also provided with three interludes between the separate movements. Encouraged to recast these into a solo work for the instrument, Aho composed a brief introduction for each interlude, functioning as a short summary of what had appeared before it in the course of the symphony. Behind the Three Interludes, and indeed the symphony, there lies a powerful experience of nature: a mid-summer journey on the Arctic Ocean, when everything, in the absence of night, was bathed in an endless blue-tinged light. Although composed 14 years later, the Symphony for Organ also owes its existence to the Eighth Symphony. After having played the organ part in a 2005 performance of that work, the Finnish organ virtuoso Jan Lehtola approached the composer urging him to write a big, multi-movement work for solo organ. Although the organ symphony has been an established genre since composers such as Charles-Marie Widor and Louis Vierne, Aho has patterned his own work on the orchestral symphony, continuing the tradition of symphonic development. All of the works musical material is related, and at the end of the finale a synthesis of it all is achieved, in what can best be described as a highly intricate and virtuosic quadruple fugue. The works subtitle, Alles Vergängliche (All that is perishable), comes from the end of Goethes Faust, and alludes to the symphonys Faustian character, reaching for the heavens, and also to its ending, as the music dies away into inaudibility